Pengembangan Sumber Daya Guru Dalam Rangka Mencapai Guru Profesional - Irene Preisilia Ilat; Erikha Loupaty (Institut Agama Kristen Negeri Manado, 2022)
The problem of human resources, especially in educational institutions, always characterizes the quality of the education produced. To improve the quality of education, professional teachers are needed. To become a professional teacher, you are required to have a higher education in the Bachelor or Diploma Four Program, competence, and an educator certificate. A professional teacher must have a theoretical basis for the work that is the concentration of his expertise. This research focuses on the aspect of developing teacher resources, especially in improving teacher professionalism, because professional teachers are the main factor in producing good quality education, in this case, quality students as a result of the education. The research was conducted at SMK Negeri 2 Manado as a school that has good qualifications and quality of education. In the development of teacher resources in order to become professional teachers at SMK Negeri 2 Manado, special attention is given to the principal so that uncertified teachers have the opportunity to develop competencies in accordance with their fields of expertise, including being included in teacher professional education and various competency development trainings. teacher.